2017
DOI: 10.1063/1.4975586
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal quenching of below-bandgap photoluminescence in InPBi

Abstract: This paper reports a temperature-dependent (10-280 K) photoluminescence (PL) study of belowbandgap electron-hole recombinations and anomalous negative thermal quenching of PL intensity in InP 1-x Bi x (x ¼ 0.019 and 0.023). Four PL features are well resolved by curve-fitting of the PL spectra, of which the energies exhibit different temperature dependence. The integral intensities of the two high-energy features diminish monotonically as temperature rises up, while those of the two low-energy features decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Such a Varshni evolution of PL energy with temperature further excludes the possibility of the feature B being related to the transition of deep level, as the energy of deep‐level emission is temperature‐insensitive. [ 36 ] As the thickness of the Ge deposition is beyond the critical thickness in the sample #GC, it is inferable that the distinctive temperature dependence of the PL energy is possibly associated with Ge tensile strain relaxation. To make further clear the influence of strain relaxation on the PL properties of the tensile‐strained Ge, it is necessary to analyze the temperature dependence of PL intensity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a Varshni evolution of PL energy with temperature further excludes the possibility of the feature B being related to the transition of deep level, as the energy of deep‐level emission is temperature‐insensitive. [ 36 ] As the thickness of the Ge deposition is beyond the critical thickness in the sample #GC, it is inferable that the distinctive temperature dependence of the PL energy is possibly associated with Ge tensile strain relaxation. To make further clear the influence of strain relaxation on the PL properties of the tensile‐strained Ge, it is necessary to analyze the temperature dependence of PL intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the PL intensity with temperature is known as an effect of negative thermal quenching (NTQ), and usually implies injection of thermally induced carriers into the transition states. [ 36,38 ] For quantitative analysis, the evolution of the PL integral intensity with temperature is fitted by a model that is taking into account the NTQ effect [ 36 ] I ( T ) = I 0 ( 1 + C 2 e E 2 / k T ) ( 1 + C 1 e E 1 / k T ) where I 0 is the integral PL intensity at 0 K, C 1 and E 1 represent the coefficient and activation energy, respectively, for a typical quenching channel, and C 2 and E 2 are the coefficient and activation energy for a carrier‐injection channel. The fitting parameters are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In addition, the randomly distributed non-radiative centers in materials can reduce overall carrier density and contribute to the thermal quenching of all kinds of PL. 9 On the other hand, negative thermal quenching (NTQ) has been observed for PL in several materials including ZnO, 10 InP 1−x Bi x , 11 Mn 4+ -activated fluoride phosphor, 12 and FASnI 3 . 13 The NTQ of PL manifests as a substantial increase of PL intensity with increasing the temperature in a certain range.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] The most commonly investigated dilute bismide system is GaAsBi, [ 8–18 ] and several research groups have demonstrated GaAsBi laser diodes. [ 19,20 ] Although there has been less research on dilute bismides in the InP system, [ 21–23 ] this system is important for longer‐wavelength applications such as fiber optic communications and infrared optics sensing. In particular, emission wavelength stability and temperature‐independent operation are highly desirable in fiber optic communication systems, and the temperature‐independent bandgap and Auger effect suppression in dilute bismide compounds with InP‐related material are expected to improve device properties.…”
Section: Introductionmentioning
confidence: 99%